Forward light scattering of first to third generation vitreous body replacement hydrogels after surgical application compared to conventional silicone oils and vitreous body - Hammer, Maximilian; Herth, Jonathan; Muuss, Marcel; Schickhardt, Sonja; Scheuerle, Alexander F.; Khoramnia, Ramin; Łabuz, Grzegorz; Uhl, Philipp; Auffarth, Gerd U. (Gels, 2023)
To treat certain vitreoretinal diseases, the vitreous body, a hydrogel composed of mostly collagen and hyaluronic acid, must be removed. After vitrectomy surgery, the vitreous cavity is filled with an endotamponade. Previously, pre-clinical hydrogel-based vitreous body substitutes either made from uncrosslinked monomers (1st generation), preformed crosslinked polymers (2nd generation), or in situ gelating polymers (3rd generation) have been developed. Forward light scattering is a measure of Stray light induced by optical media, when increased, causing visual disturbance and glare. During pinhole surgery, the hydrogels are injected into the vitreous cavity through a small 23G-cannula. The aim of this study was to assess if and to what extent forward light scattering is induced by vitreous body replacement hydrogels and if Stray light differs between different generations of vitreous body hydrogel replacements due to the different gelation mechanisms and fragmentation during injection. A modified C-Quant setup was used to objectively determine forward light scattering. In this study, we found that the 1st and 3rd generation vitreous body replacements show very low stray light levels even after injection (2.8 +/− 0.4 deg2/sr and 0.2 +/− 0.2 deg2/sr, respectively) as gel fragmentation and generation of interfaces is circumvented. The 2nd generation preformed hydrogels showed a permanent increase in stray light after injection that will most likely lead to symptoms such as glare when used in patients (11.9 +/− 0.9 deg2/sr). Stray light of the 2nd generation hydrogels was 3- and 2-fold increased compared to juvenile and aged vitreous bodies, respectively. In conclusion, this significant downside in the forward light scattering of the 2nd generation hydrogels should be kept in mind when developing vitreous body replacement strategies, as any source of stray light should be minimized in patients with retinal comorbidities.
Gesehen am 29.11.2023